EVALUATION OF A FALLS PREVENTION PROGRAM FOR THE RURAL ELDERLY - Coughlin, DaRae M. (My University, 2010)
Falls are a major concern in the elderly population because of the significant impact on health status and quality of life. Falls are the leading cause of unintentional deaths in persons 65 and older. Modifiable risk factors associated with falls, as well as single and multi-factorial falls prevention programs, have been studied in the urban elderly. However, there is a dearth of literature on the effectiveness of falls prevention programs in the rural elderly population. The purpose of this study was to determine the effectiveness of an on-going multi-factorial falls prevention program in Wisconsin -- the Sure Step Falls Prevention (SSFP) program -- in decreasing the rate of falls in rural elderly participants. Pender?s Health Promotion Model was used as the theoretical framework for this study. A pre-post design was used to determine the effectiveness of the SSFP program in the rural elderly. A convenience sample of 67 elderly participants who met the inclusion criteria for the SSFP, and who completed the pre- and post-intervention questionnaires, was obtained from the SSFP existing data set. Pre- and post- intervention data were collected for analysis. Data were analyzed using descriptive and inferential statistics. Falls rate ratios and paired t-tests were used for comparison of pre- and post-intervention data within groups. Repeated measures ANOVA testing was utilized to compare data between groups. Findings of the study revealed that there was a significant reduction in the rate of falls in both the rural and non-rural groups. The rural group had a 65% reduction in the mean rate of falls 6 months post-intervention. The non-rural group had a 50% reduction in the mean rate of falls 6 months post-intervention. The operational definition for effectiveness of a falls prevention program stated a 33% reduction in falls rate constituted an effective intervention, and both the rural and non-rural group met and surpassed this definition of effectiveness for a falls intervention. In addition, the results of this study revealed there was not a significant difference in the reduction of mean rate of falls 6 months post-intervention between the rural and non-rural group, despite a lack of healthcare resources available to the rural elderly, as described in the literature.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science in Nursing Family Nurse Practitioner
Keywords: Old age assistance; Older people services for; Behavior modification; Aging